Pax - Pennypacker, Sara; Klassen, Jon (New York Balzer + Bray, 2016)
"After being forced to give up his pet fox Pax, a young boy named Peter decides to leave home and get his best friend back"--
103510
Keywords: Foxes as pets; Human-animal relationships; Juvenile Fiction -- Social Issues -- Friendship; Juvenile Fiction -- Animals -- Foxes; Juvenile Fiction -- Nature & the Natural World -- General (see also headings under Animals).; Fiction; Juvenile works